Direct comparison of the accuracy of preoperative high-sensitivity cardiac troponin T to predict mortality, acute heart failure and perioperative myocardial infarction/injury after non-cardiac surgery. (25th November 2020) - Gualandro, D; Puelacher, C; Liffert, M; Arslani, K; Meister, R; Glarner, N; Luratibuse, G; Cardozo, F.A; Bolliger, D; Steiner, L; Caramelli, B; Osswald, S; et al.
Abstract: Background: Death, acute heart failure (AHF) and perioperative myocardial infarction/injury (PMI) are the most relevant cardiovascular complications following non-cardiac surgery. Unfortunately, the incidence of these complications are higher than expected. Currently available tools to predict these complications have only modest accuracy. Purpose: To determine the accuracy of preoperative high-sensitivity cardiac troponin T (hs-cTnT) concentrations for prediction of mortality, AHF and PMI after non-cardiac surgery. Methods: We prospectively included 4, 709 patients at high cardiovascular risk undergoing non-cardiac surgery. Hs-cTnT concentrations were measured before surgery and, daily after surgery, for two days. PMI was defined as an absolute increase of 14ng/L (the 99th percentile of the assay used) from hs-cTnT baseline values. The primary endpoint was the diagnostic accuracy of preoperative hs-cTnT concentration to predict death, AHF and PMI within 30 days, as quantified by the area under the receiving-operating curve (AUC). Multivariate logistic regression analysis was performed to test the association between preoperative hs-cTnT and each endpoint. Results: All-cause mortality occurred in 133 (3%), AHF in 84 (2%) and PMI in 742 (16%) patients. Preoperative hs-cTnT concentrations had good accuracy for prediction of death, AHF and PMI (AUC = 0.75 [95% CI, 0.71–0.79], 0.72 [95% CI, 0.67–0.77] and 0.73 [95% CI, 0.71–0.75], respectively). After adjusting for confounders, hs-cTnT remained an independent predictor for death with an adjusted odds ratio (aOR) of 2.1 (95% CI, 1.7–2.7, P<0.001) and for PMI (aOR 2.2, 95% CI, 1.9–2.4, P<0.001), but not for AHF (aOR 1.0, 95% CI, 0.7–1.4, P=0.99). An hs-cTnT concentration below 5ng/L was found in 526 (11%) patients, and this cut-off yielded a negative predictive value of 99.6% for the occurrence of death, 99.2% for AHF and 95.6% for PMI. Conclusion: The preoperative hs-cTnT concentration has a good accuracy to predict mortality, AHF and PMI after non-cardiac surgery, but is an independent predictor only for mortality and PMI. A cut-off value of 5ng/L identifies a subgroup of patients at low risk for these complications. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Swiss National Foundation, Swiss Herat Foundation